منهج النبي صلى الله عليه وسلم في الكشف عن مواهب الصحابة وتنميتها: Prophet Mohammad's (PHUH) methods of discovering and developing his companions talents - Naeem Bustanji (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث الكشف عن الموهوبين بجانبيه النظري والعملي، وتنمية مواهبهم وتوظيفها، يعد من العلوم التي غدت قائمة بذاتها، ولأنَّ السنة النبوية تنادي بالعلم والابتكار، وترفض الجمود والتقليد، فقد أعطت هذا الجانب أهمية بالغة يمكن ملاحظتها وتتبع تطبيقاتها في السنة النبوية. تتمثل مشكلة هذه في الدراسة في بيان منهج النبي صلى الله عليه وسلم في الكشف عن مواهب الصحابة رضي الله عنهم، والمؤشرات التي استند إليها في تصنيف هذه المواهب، والوسائل التي سلكها في تنمية هذه المواهب وتطويرها، مبيناً المخرجات العملية والنظرية لهذا التطوير على الجانب الشخصي والاجتماعي والدعوي، وهو ما هدف الباحث إلى بيانه، ليخلص إلى أن النبي صلى الله عليه وسلم كان سباقاً في هذا المجال، وبأسلوب مرن سلك فيه طرق دقيقة في الكشف عن مواهب الصحابة، تمثلت في الملاحظة والترشيح والاختبارات، بانياً أحكامه على هذه المواهب بروية وحكمة. ABSTRACT Revealing, developing and investment of talents have been one of the main distinct branches of science in recent years because AL-Sunnah AL-Nabawia has been calling for science and innovations and has been against stagnation and convention, it gave much importance to this respect which can be easily noticed. In this study, the researcher has traced the Prophet's approach in revealing his companions talents and in the indicators he depended on in classifying those talents and the means he used in developing them the researcher has also shown the practical and theoretical outcomes of this developing on the individual, social aspect and Da'wa(call of the Islam) This is what the aim of searching for is his explanation, to conclude that the Prophet, may God bless him and grant him peace, was a pioneer in this field, and in a flexible manner in which he followed precise methods in discovering the talents of the Companions, represented by choices, nominations, and tests, and in order to practice these talents carefully and wisely.